Development of Palagsing (Sticky Sago Palm Cake) with extended shelf life through water retort processing - Remollo, Alvier Jade B.; Peralta, Justin Godfrey B. (Quezon City College of Home Economics, University of the Philippines Diliman, 2023)
Palagsing is a local delicacy from Butuan City made of Sago palm flour, locally known as unaw, young coconut meat, and brown sugar. Similar to other rice cake products (kakanin), Palagsing has a shelf life of less than a day. This study was conducted to determine the effect on quality, consumer acceptability, and shelf life of water-retort processed Palagsing and compared it to the traditionally processed samples. Two separate batches of Palagsing were used in this study. The first batch was subjected to traditional processing in which the samples were boiled for 30 minutes and vacuum-packed after cooling. The second batch, on the other hand, was vacuum-packed using retortable pouches and was subjected to a retort process at 121 C, with a minimum F value of 4. Both samples were stored in the refrigerator at 4 C for ten days. Retorted Palagsing was found to have a significantly low percent moisture content, firmness value, and a stable pH during the storage period compared to the boiled-only counterparts. Results also showed that retorted Palagsing was microbially safe during the storage period from Day Zero to 10. Meanwhile, the traditionally prepared sample was unfit for human consumption on day 10. Sensory evaluation of the products revealed that water-retort processed Palagsing obtained high mean values in all sensory attributes and overall consumer acceptability.
Thesis (Bachelor of Science in Food Technology) -- University of the Philippines Diliman
Bibliography: pages 38-45.
Keywords: Consumer behavior -- Philippines; Food -- Philippines